2015
DOI: 10.1371/journal.pone.0141536
|View full text |Cite
|
Sign up to set email alerts
|

Ancient Genetic Signatures of Orang Asli Revealed by Killer Immunoglobulin-Like Receptor Gene Polymorphisms

Abstract: The aboriginal populations of Peninsular Malaysia, also known as Orang Asli (OA), comprise three major groups; Semang, Senoi and Proto-Malays. Here, we analyzed for the first time KIR gene polymorphisms for 167 OA individuals, including those from four smallest OA subgroups (Che Wong, Orang Kanaq, Lanoh and Kensiu) using polymerase chain reaction-sequence specific primer (PCR-SSP) analyses. The observed distribution of KIR profiles of OA is heterogenous; Haplotype B is the most frequent in the Semang subgroups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…Previous studies have shown that KIR2DL2 is in the linkage disequilibrium with KIR2DS2, which caused the relative activation of KIR receptor, which is responsible for the loss of recognition of HLA-C [60][61][62] . The different ethnic populations showed different values of KIR polymorphisms in elucidating genetic relationships among human populations 63 . Moreover, HLA genotyping is traditionally performed using a serological method.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that KIR2DL2 is in the linkage disequilibrium with KIR2DS2, which caused the relative activation of KIR receptor, which is responsible for the loss of recognition of HLA-C [60][61][62] . The different ethnic populations showed different values of KIR polymorphisms in elucidating genetic relationships among human populations 63 . Moreover, HLA genotyping is traditionally performed using a serological method.…”
Section: Discussionmentioning
confidence: 99%
“…The Orang Asli are the indigenous people of Peninsular Malaysia and the estimated population size is only ~180,000 people [31]. The Senoi tribe, which consists of six sub-tribes (Che Wong, Jahut, Mah Meri, Semoq Beri, Semai and Temiar) formed the largest group of Orang Asli with ~ 98,000 people followed by the Proto-Malays with ~75,000 people from 6 sub-tribes (Kanaq, Kuala, Seletar, Jakun, Semelai and Temuan) and the smallest group are those that expressed the negrito phenotypes (Bateq, Jahai, Kensiu, Kintaq, Mendriq and Lanoh) with an estimated number of only 5,000 people [32]. Their settlements are scattered across the Peninsular Malaysia whereby the Negritos and Senoi are generally localized in the northern and central regions while Proto-Malays settlements are found in the central and southern regions [33].…”
Section: Discussionmentioning
confidence: 99%
“…The Malay group represents Deutero‐Malays, whose ancestors settled in Malaysia 3–5000 years ago 32 and subsequently admixed with immigrants from multiple origins including Arabs, Chinese and Indians. Previous studies of KIR diversity in Malaysians were limited to low‐resolution analyses 33–35 . In the current study, we characterized the KIR and HLA genes of 92 Malay and 75 Malaysian Chinese individuals at high resolution using targeted high‐throughput sequencing technology, and then compared them with available data from other populations.…”
Section: Introductionmentioning
confidence: 99%